The Rising sea level – a threat to statehood - Mbatia, Kelvin (Strathmore University, 2019)
Climate change has several adverse effects. One of these, sea level rise, threatens two key requirements for statehood, as listed in the Montevideo Convention on the Rights and Duties of States, and backed by the Declaratory Theory of Statehood. These are: a defined territory and permanent population. This paper illustrates the interplay between the rising sea level, on the one hand, and the maritime boundaries of, and populations residing in, small low-lying island nations, on the other. It suggests that a rise in sea level interferes with the maritime boundaries of these nations, which are determined by ambulatory baselines. It argues that a consistent rise in sea level, by submerging small island nations, will lead to their extinction. Furthermore, the rising sea will displace large numbers of people on these island nations. These effects impugn the statehood of these nations.
Research Brown Bag Presentation
Keywords: Climate change; Statehood; Maritime